Electrochemical Oxidation of Benzylic C(sp3)–H Bonds Presents a Versatile Metal-Free Approach for the Synthesis of Enones - Yavari, Issa; Shaabanzadeh, Sina (Synthesis, 2025)
An electrochemical approach has been developed for synthesizing enones with various functional groups through the electrooxidation of benzylic substrates in an aqueous solution containing a methyl ketone. This method eliminates the necessity for hazardous metal catalysts and external oxidants. It demonstrates impressive chemical yields ranging from 68% to 80%, is scalable for gram-scale production, and achieves Coulombic yields between 10% and 15%.
Keywords: Electrochemical oxidation; Enones; Benzylic C(sp3)–H bond; Methyl ketones; Aldol condensation